2015
DOI: 10.1007/s11664-015-3692-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of Hybrid-Organic Memory Devices Based on Au Nanoparticles

Abstract: We report on the fabrication and characterization of hybrid-organic memory devices based on gold (Au) nanoparticles that utilize metal-insulator-semiconductor structure. Au nanoparticles were produced by sputtering and inertgas condensation inside an ultrahigh-vacuum compatible system. The nanoparticles were self-assembled on a silicon dioxide (SiO 2 )/silicon (Si) substrate, then coated with a poly(methyl methacrylate) (PMMA) insulating layer. Aluminum (Al) electrodes were deposited by thermal evaporation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Organic memory devices play an important part in plastic and flexible electronic applications [19], which lead to extensive research in this field. Organic memory devices based on charge storage in bistable switching [20][21][22], metal-insulator-semiconductor structures (MIS) [23][24][25][26], and organic thin film memory transistors (OTFMTs) [27][28][29] have been reported in recent years. The main structure to achieve fast and high capacity memory is the floating gate-based memory devices; where a thin film of a floating gate serves as the charge storage element in a transistor or MIS structure [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Organic memory devices play an important part in plastic and flexible electronic applications [19], which lead to extensive research in this field. Organic memory devices based on charge storage in bistable switching [20][21][22], metal-insulator-semiconductor structures (MIS) [23][24][25][26], and organic thin film memory transistors (OTFMTs) [27][28][29] have been reported in recent years. The main structure to achieve fast and high capacity memory is the floating gate-based memory devices; where a thin film of a floating gate serves as the charge storage element in a transistor or MIS structure [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Organic memory devices play a major role in plastic and flexible electronic applications [10], which lead to extensive research in this domain. Organic memory devices, based on charge storage in bistable switching [11,12,13], metal-insulator-semiconductor structures (MIS) [14,15,16,17], and organic thin film memory transistors (OTFMTs) [18,19,20,21] have been reported in the last 20 years. One of the well-known memory structures is the floating gate-based memory device; where typically a thin film of a floating gate serves as a charge storage node in a transistor or MIS structure.…”
Section: Introductionmentioning
confidence: 99%
“…One of the well-known memory structures is the floating gate-based memory device; where typically a thin film of a floating gate serves as a charge storage node in a transistor or MIS structure. It is reported that stable memory behaviour can be achieved by charging nanoparticles or nanowires, which are integrated into the insulating layer of the MIS structures or thin film transistors [14,19]. When a program voltage is applied between the gate and the source contact, electronic charges can be transferred onto the floating gate by quantum tunneling or thermal emission, charging the floating gate and changing the transistor’s threshold voltage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations